Delayed luminescence spectroscopy of organic photovoltaic binary blend films: Probing the emissive non-geminate charge recombination - Keivanidis, Panagiotis E.; Kamm, Valentin; Dyer-Smith, Clare; Zhang, Weimin; Laquai, Frédéric; McCulloch, Iain; Bradley, Donal D.C.; Nelson, Jenny (My University, 2010)
Organic photovoltaics: Following the direct photoexcitation of the low-energy optical gap PDI component in the F8BT:PDI photovoltaic blend film (step 1), charge generation takes place (steps 2, 3). Non-geminate charge recombination (step 4) results in the generation of delayed luminescence (DL) in the μs time scale (step 5). The DL spectrum originates from an equilibrated charge-transfer (CT) state formed between the components of the composite. The F8BT-PDI CT complex has a ground state character (step 6). Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: bulk heterojunction; charge transfer; delayed luminescence; microstructure; non-geminate charge recombination; Solar cells